Bent helical structure in kinetoplast DNA - Marini, Joan C. (1982)
We have investigated the unusual physical properties of a restriction fragment of Leishmania tarentolae kinetoplast DNA. A gel-purified fragment comprising slightly more than half of a minicircle was determined by Maxam-Gilbert sequence determination to be 490 base pairs (bp) in length. This fragment has dramatically anomalous electrophoretic behavior; it has an apparent size of 450 bp on a 1% agarose gel but migrates as 1,380 bp on a 12% polyacrylamide gel. However, in gel filtration on Sephacryl S-500, the fragment elutes with an apparent size of 375 bp. Finally, it behaves anomalously in electric dichroism experiments. Field-free rotational relaxation times from transient electric dichroism studies are highly sensitive to effective molecular dimensions. The rotational relaxation time of the kinetoplast fragment is smaller than that of a 309-bp control fragment from pBR322. Because rigorous control experiments rule out the possibility that this fragment is modified, these anomalous properties must be dictated by the sequence itself. Fragment behavior indicates that it has an unusually compact configuration; we propose that this molecule contains a region of systematically bent B-DNA. This model accounts for the fragment's difficulty in snaking through the pores of a polyacrylamide gel, its ease in diffusing into Sephacryl beads, and its smaller rotational relaxation time. Bending of this molecule may be caused by periodicities in the DNA sequence.